Patient‐based cost‐effectiveness analysis of FOLFIRI versus FOLFOX7 for advanced gastric adenocarcinoma in China: A 4‐year prospective randomised phase II study. (11th December 2019) - Wen, Feng; Zheng, Hanrui; Zhang, Pengfei; Zhou, Jing; Chen, Hongdou; Zhou, Kexun; Li, Qiu; Bi, Feng
Abstract: Background: Using data from the 4‐year follow‐up results of an open, randomised, phase II study, this patient‐based cost‐effectiveness analysis compares mFOLFIRI (irinotecan, 5‐fluorouracil and leucovorin, the IRI arm) with mFOLFOX7 (oxaliplatin, 5‐fluorouracil and leucovorin, the OXA arm) as first‐line treatments in patients with locally advanced gastric adenocarcinoma (GC). Methods: A Markov model was created based on previous results reported at the 2016 Gastrointestinal Cancers Symposium to evaluate mFOLFIRI and mFOLFOX7 for advanced GC quality‐adjusted life years (QALYs), and incremental cost‐effectiveness ratios (ICERs) were examined as the primary outcomes. Results: For the evaluable 128 patients, treatment efficacy was 0.59 QALYs for the IRI arm and 0.70 QALYs for the OXA arm, with a total cost of $13, 861.34 for the IRI arm and $14, 127.30 for the OXA arm. Hence, the ICER was $2, 417.82 per QALY the OXA arm, which was below the threshold of 3 × per capita GDP of China. For subgroup analysis of those receiving mFOLFIRI followed by mFOLFOX7 (the IRI arm) and the reverse (the OXA arm), the OXA arm gained 0.44 more QALYs than the IRI arm with a total cost of $28, 890.09 for the IRI arm and $31, 147.30 for the OXA arm. However, the cost per QALY was also lower for the OXA arm than for the IRI arm, and the cost per QALY gained was $5, 129.55 (below the Chinese WTP). Conclusion: mFOLFOX7 is a very high cost‐effective alternative as the first‐line treatment for those patients with advanced GC compared with mFOLFIRI.